Zinc oxide nano- and micro-crystals synthesised by co-precipitation and hydrothermal process. (July 2014) - Chen, G.; Liu, F.; Mo, Z.; Zhang, B.; Zhang, H.; Zhang, J.; Yan, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Micro-sized zinc oxide (ZnO) crystals with different shapes (spindle-like, flower-like and rod-like) were successfully synthesised by a simple co-precipitation and hydrothermal reaction using zinc chloride, Pluronic F127 (PF127) and NH3.H2O as raw materials. The results from X-ray diffraction and scanning electron microscopy show that the morphology and size of the ZnO were strongly dependent on the content of NH3.H2O, and the aspect ratio of ZnO crystals is also controlled by PF127. The presence of enough hydroxyl ions (OH−) can polish and modify the morphology of ZnO in the hydrothermal system, but the hexagonal cylinder rods disappear in a strong basic environment. As the content of PF127 increases, the aspect ratio of the ZnO rods also increases. If the amount of PF127 is excessive, the average aspect ratio is reduced. Systematic reactions in the presence of different environments were conducted to control the formation of various well shaped ZnO crystals.